The effect of information technology training and managerial support on employee performance mediated by emotional intelligence - Agung Surya Dwianto; Pupung Purnamasari; Periansya, Periansya (SEAN Institute, 2024)
This research explores the complex interplay between Information Technology Training (ITT), Managerial Support (MS), Emotional Intelligence (EI), and Employee Performance (EP) within the organizational context of PT Bimasakti Multi Sinergi in Yogyakarta. Through a quantitative approach and utilizing Structural Equation Modeling (SEM) with the Smart PLS technique, the study investigates both direct and indirect effects to unravel the nuanced relationships among these variables. The results indicate that IT Training significantly influences both Emotional Intelligence and Employee Performance, highlighting the dual impact of technical skill development. Managerial Support directly influences Employee Performance but lacks a significant indirect effect through Emotional Intelligence. Emotional Intelligence emerges as a significant mediator, bridging the relationship between IT Training and Employee Performance. These findings underscore the importance of a comprehensive approach to employee development, emphasizing both technical proficiency and emotional intelligence within the evolving dynamics of a technology-driven workplace. The insights contribute to refining organizational strategies for optimizing employee performance in contemporary business environments